Reconstructing rainfall using dryland dunes: Assessing the suitability of the southern Kalahari for unsaturated zone hydrostratigraphies - Stone, Abi; Zeng, Yijian; Yu, Lianyu; van der Ploeg, Martine; Wanke, Heike (Frontiers in Earth Science, 2022)
Time-series of dryland rainfall over 100 to 1000s of years are scarce but are needed to underpin improved predictions under future climate change. Dryland sand dunes are established Quaternary geomorphic archives, which also contain pore moisture as part of the unsaturated zone (USZ) with chemical tracers that provide a novel proxy for palaeomoisture. Chloride depth profiles, converted using a mass balance approach to temporal records, are known as hydrostratigraphies. Evaporative enrichment of meteoric chloride occurs in the near-surface zone and the established signature gets transported vertically via infiltration. This study explores the potential for this approach for southern Kalahari vegetated linear dunes comparing twelve (10-12 m deep) hydrostratigraphies across space and sampled in different years (2011, 2013 and 2016). Three further profiles sampled close to an interdune pan demonstrate that additional chloride is added locally to the dune closest to the pan. The remaining hydrostratigraphies show variable trends, with four broad groupings, leading us to suggest this region is unsuitable for this approach. Insights into this variable behavior were sought from simulating liquid and vapor flux using STEMMUS (Simultaneous Transfer of Energy, Mass and Momentum in Unsaturated Soil). Simulations suggest the mixing zone can reach 10 m thick, which helps account for the variation in hydrostratigraphies. Heterogeneity may also arise from spatially-heterogenous receipt of convective rainfall events and non-uniform vegetation cover. Furthermore, the vegetated nature of the landscape leads to less uniform moisture movement within the dune sands. We call for future applications to include site-specific insights into moisture dynamics.